COSMETICS ADVERTISEMENT LANGUAGE THROUGH DISCURSIVE PSYCHOLOGY - ARJULAYANA, ARJULAYANA; ENAWAR, ENAWAR (Linguists : Journal of Linguistics and Language Teaching, 2022)
This paper looked into the language used in the advertisement of anti-aging cream based on a discursive psychology approach. The language used in the advertisement mainly raises the women's interest, especially when they hear the word "anti-aging" to resist aging skin, although the old may not be manipulated. This discursive research psychology is the approach used to give an understanding of the discourse phenomenon to show the contribution of creating women's social activity for their lifestyle. The language used in the online advertising course was the research data in this research. The data collection is based on the language used in online advertising discourse based on five kinds of cosmetics advertisement and 12 carrier women with 30-45 years old who lived in Jakarta. The qualitative descriptive is used to explain the phenomenon and social phenomena related to advertisement discourse and women's needs; then, the data were analyzed based on the interview. This research finding shows that, firstly, the advertisement's implicit meaning encourages and drives customers' psychology to try cosmetics. Secondly, the advertisement language's explicit meaning is propagated and seems exaggerated. Thirdly, the advertisement language encourages customers to buy the product due to the social relation and lifestyle.